2018
DOI: 10.1891/0886-6708.v33.i2.193
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Stalking and the Severity of Intimate Partner Abuse

Abstract: Using data from the Chicago Women’s Health Risk Study (N = 464), this study examined the intersection of stalking and the severity of intimate partner abuse while controlling for previously identified risk factors of intimate partner homicide. Findings indicate that (a) victims of life-threatening abuse by an intimate partner were significantly more likely toexperience stalking than victims of nonlethal abuse; (b) after controlling for key risk factors, stalking increased the risk of life-threatening abuse; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Others have underscored the importance of recognizing the nexus between IPV and stalking (Logan & Walker, 2009), given the escalation of violence, potential harm, even lethality that a stalking perpetrator may inflict on a current or former intimate partner. Partner-perpetrated stalking has been identified as more dangerous, consisting of longer duration, and producing significantly more harm than stranger-perpetrated stalking (Brady & Hayes, 2018; Logan et al, 2007; Logan & Walker, 2010; McFarlane et al, 1999; Mechanic et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Others have underscored the importance of recognizing the nexus between IPV and stalking (Logan & Walker, 2009), given the escalation of violence, potential harm, even lethality that a stalking perpetrator may inflict on a current or former intimate partner. Partner-perpetrated stalking has been identified as more dangerous, consisting of longer duration, and producing significantly more harm than stranger-perpetrated stalking (Brady & Hayes, 2018; Logan et al, 2007; Logan & Walker, 2010; McFarlane et al, 1999; Mechanic et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These selection criteria were chosen for two reasons. First, some scholars have argued that relationship history, as well as the heightened risk for violence (Brady & Hayes, 2018; McFarlane et al, 2002), renders partner stalking experiences distinct from cases involving acquaintance or stranger stalkers (Logan, 2010; Logan & Walker, 2009). Consequently, criminal justice decision-makers with limited experience or training on stalking may rely on perceptual shorthand that results in them overlooking, minimizing, and/or treating unwanted pursuit behaviors and violence by an intimate partner as DV rather than as a course of conduct that could also warrant stalking charges (Brady & Nobles, 2017; Klein et al, 2009; Scott et al, 2013; Tjaden & Thoennes, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Sheridan et al, 2001), there still remain a number of research questions that have yet to be addressed. In particular, given that stalking is a risk factor for severe IPV (Brady & Hayes, 2018) and femicide (McFarlane et al, 2002; Spencer & Stith, 2018), examining how the criminal justice system responds to stalking complaints is the next logical step to enhancing homicide prevention initiatives. Research on this topic, however, has not only yielded more questions than answers, but alarming concerns for suspect accountability.…”
Section: Introductionmentioning
confidence: 99%
“…This raises questions related to the capacity of officers to identify stalking behaviors in DV complaints and to what extent aspects of the case influence action or inaction. Overlooking the possibility of stalking in cases involving current or former intimate partners could potentially be a lethal (J. C. Campbell et al, 2003;McFarlane et al, 1999McFarlane et al, , 2002Spencer & Stith, 2018) or near-lethal mistake (Brady & Hayes, 2018).…”
Section: Policing Stalking Complaintsmentioning
confidence: 99%
“…Stalking is a crime in all 50 states that occurs when someone repeatedly engages in behaviors directed at a specific person that would make a reasonable person fear for the safety of themselves or others (National Center for Victims of Crime, 2007). Stalking is a serious form of coercive control that is often associated with severe intimate partner violence and femicide (Brady & Hayes, 2018; J. C. Campbell et al., 2003; McFarlane et al., 2002; Spencer & Stith, 2018). In fact, a recent meta-analysis of 17 intimate partner homicide studies found that stalking produced a threefold increase in the risk of homicide among female victims by male partners (Spencer & Stith, 2018).…”
mentioning
confidence: 99%